Alternative skin sensitization prediction and risk assessment using proinflammatory biomarkers, interleukin-1 beta (IL-1β) and inducible nitric oxide synthase (iNOS). Issue 5 (4th March 2019) - Kim, Min Kook; Kim, Kyu-Bong; Kim, Hyung Sik; Lee, Byung-Mu
ABSTRACT: As an alternative to animal tests for skin sensitization potency and risk assessment, cell viability and biomarkers related to skin sensitization were analyzed in THP-1 human monocytic leukemia cells. Cell viabilities of 90% (CV90) and 75% (CV75) were determined for 24 selected test chemicals. Further biomarkers related to skin sensitization were also determined under equivalent comparative conditions. In cell viability analyses, potent skin sensitizers exhibited high cytotoxicity, but non-sensitizers did not display this tendency. In biomarker analyses, interleukin-I beta (IL-1β), inducible nitric oxide synthase (iNOS), IL-1β+iNOS, and THP-1 IL-1β+Raw 264.7 IL-1β were found to be suitable for prediction of skin sensitization potency following classification as either skin sensitizers or non-sensitizers (accuracies of 91.7%, 87.5%, 83.3%, and 82.6%, respectively). A significant positive correlation was found between biomarkers and skin sensitization potency, with a correlation coefficient (R) of 0.7 or more (correlation coefficients of 0.77, 0.72, 0.7, and 0.84, respectively). Finally, the skin sensitization potency effective threefold concentration (EC) 3% was predicted using a biomarker equation, with resulting prediction rates (match rate with actual data) of 58.3%, 54.2%, 62.5%, and 60.9%, respectively. The prediction accuracy for the EC3 value obtained from animal data was calculated as 83.3%, 79.2%, 79.2%, and 73.9%, respectively. Thus, these biomarkers, IL-1β and iNOS, may be alternatively used to predict skin sensitization potency and risk assessment.